2024
DOI: 10.1177/0272989x231220954
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Smoking Status in Making Risk-Informed Diagnostic Decisions in the Lung Cancer Pathway: A Qualitative Study of Health Care Professionals and Patients

Georgia B. Black,
Sam M. Janes,
Matthew E. J. Callister
et al.

Abstract: Background Lung cancer clinical guidelines and risk tools often rely on smoking history as a significant risk factor. However, never-smokers make up 14% of the lung cancer population, and this proportion is rising. Consequently, they are often perceived as low-risk and may experience diagnostic delays. This study aimed to explore how clinicians make risk-informed diagnostic decisions for never-smokers. Methods Qualitative interviews were conducted with 10 lung cancer diagnosticians, supported by data from inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Every year, millions of individuals suffer illnesses and lose their lives due to the consumption of tobacco in various forms [ 2 ]. Many researchers have suggested that long-term cigarette smoking is linked to a higher likelihood of various medical conditions that can potentially impact brain neurobiology and neurocognition, either directly or indirectly [ 3 , 4 ]. In cross-sectional studies focusing on smokers who are middle-aged and/or in older adulthood, researchers have noted that smokers exhibit poorer cognitive performance in multiple areas compared to non-smoking control groups [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Every year, millions of individuals suffer illnesses and lose their lives due to the consumption of tobacco in various forms [ 2 ]. Many researchers have suggested that long-term cigarette smoking is linked to a higher likelihood of various medical conditions that can potentially impact brain neurobiology and neurocognition, either directly or indirectly [ 3 , 4 ]. In cross-sectional studies focusing on smokers who are middle-aged and/or in older adulthood, researchers have noted that smokers exhibit poorer cognitive performance in multiple areas compared to non-smoking control groups [ 5 ].…”
Section: Introductionmentioning
confidence: 99%